1995
DOI: 10.1007/bf00203400
|View full text |Cite
|
Sign up to set email alerts
|

Variations in peroxisomal catalase of neonatal rat hepatocyte subpopulations

Abstract: Alcohol consumption during pregnancy is teratogenic and induces severe alterations in hepatocytes. In the hepatocyte peroxisomal system, ethanol is converted in the presence of H2O2 to acetaldehyde and water. Therefore, peroxisomal catalase also acts as an antioxidant defence mechanism by removing H2O2 and preventing the formation of hydroxyl radicals in the cell. Alterations in peroxisomal catalase after pre- and pre+postnatal alcohol exposure were investigated in the rat. The effect of pre- and postnatal exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…CAT, a pivotal antioxidant enzyme, can decompose hydrogen peroxide into oxygen and H 2 O. 34 The later results showed that clivorine at the low concentration increased CAT activity weakly, suggesting the possible increase of cellular defensive capacity. The increase of CAT activity also indicates that CAT may play important roles in regulating clivorine-induced toxicity on rat hepatocytes.…”
Section: Discussionmentioning
confidence: 96%
“…CAT, a pivotal antioxidant enzyme, can decompose hydrogen peroxide into oxygen and H 2 O. 34 The later results showed that clivorine at the low concentration increased CAT activity weakly, suggesting the possible increase of cellular defensive capacity. The increase of CAT activity also indicates that CAT may play important roles in regulating clivorine-induced toxicity on rat hepatocytes.…”
Section: Discussionmentioning
confidence: 96%